Antimycobacterial, Enzyme Inhibition, and Molecular Interaction Studies of Psoromic Acid in Mycobacterium tuberculosis: Efficacy and Safety Investigations - Hassan, Sherif T S; Šudomová, Miroslava; Berchová-Bímová, Kateřina; Gowrishankar, Shanmugaraj; Rengasamy, Kannan R R (Journal of clinical medicine, 2018)
The current study explores the antimycobacterial efficacy of lichen-derived psoromic acid (PA) against clinical strains of Mycobacterium tuberculosis (M.tb). Additionally, the inhibitory efficacy of PA against two critical enzymes associated with M.tb, namely, UDP-galactopyranose mutase (UGM) and arylamine-N-acetyltransferase (TBNAT), as drug targets for antituberculosis therapy were determined. PA showed a profound inhibitory effect towards all the M.tb strains tested, with minimum inhibitory concentrations (MICs) ranging between 3.2 and 4.1 µM, and selectivity indices (SIs) ranging between 18.3 and 23.4. On the other hand, the standard drug isoniazid (INH) displayed comparably high MIC values (varying from 5.4 to 5.8 µM) as well as low SI values (13.0⁻13.9). Interestingly, PA did not exhibit any cytotoxic effects on a human liver hepatocellular carcinoma cell line even at the highest concentration tested (75 µM). PA demonstrated remarkable suppressing propensity against UGM compared to standard uridine-5'-diphosphate (UDP), with 85.8 and 99.3% of inhibition, respectively. In addition, PA also exerted phenomenal inhibitory efficacy (half maximal inhibitory concentration (IC50) value = 8.7 µM, and 77.4% inhibition) against TBNAT compared with standard INH (IC50 value = 6.2 µM and 96.3% inhibition). Furthermore, in silico analysis validated the outcomes of in vitro assays, as the molecular interactions of PA with the active sites of UGM and TBNAT were unveiled using molecular docking and structure⁻activity relationship studies. Concomitantly, our findings present PA as an effective and safe natural drug plausible for use in controlling tuberculosis infections.
Keywords: antitubercular drug; drug resistance; arylamine N-acetyltransferase; UDP-galactopyranose mutase; drug design; psoromic acid